Advancing knowledge of One Health in China: lessons for One Health from China's dengue control and prevention programs - Xinyu Feng; Na Jiang; Jinxin Zheng; Zelin Zhu; Junhu Chen; Lei Duan; Peng Song; Jiahui Sun; Xiaoxi Zhang; Lefei Hang; Yang Liu; Renli Zhang; et al. (Science in One Health)
Background: The emergence of dengue fever has prompted significant public health responses, highlighting the need for a comprehensive understanding of One Health in addressing vector-borne diseases. China's experience in dengue control and prevention programs offers valuable insights into the successful integration of multidisciplinary strategies. Aims: The review aims to: (1) systematically analyze lessons from China's dengue control and prevention programs, focusing on the integration of these efforts with the One Health approach; (2) underscore the reasons of optimizing the dengue control and prevention program; (3) highlight the alignment of China's dengue control strategies with the One Health framework; (4) contribute to global efforts in combating dengue, providing scientific evidence and strategic recommendations for other regions facing similar challenges. Results: Through a comprehensive literature review and expert interviews, this study found China's approach to dengue control and prevention implemented through a hierarchical system led by the government, with collaborative efforts across multiple departments. This multi-sectoral collaboration mechanism enables the technical interventions well executed by health and disease control institutions, optimizing the integration of multiple cost-effeteness approaches, such as case management, early detection and outbreak response, reducing local transmission, and minimizing severe cases and fatalities. It was found that community participation and public health education have played a vital role in raising awareness, promoting personal protective measures, and enhancing the overall effectiveness of control efforts. The implementation of these integrated interventions has resulted in reduced dengue cases and improved capacity of outbreak response. China's dengue control strategies under the One Health framework, with focus on interdisciplinary collaboration, incorporated environmental and ecological interventions, which reduced mosquito breeding sites and improved sanitation. The findings of the review underscore the need for continuous improvement in early warning systems, scientific research, and the adoption of the One Health approach to address emerging challenges posed by climate change and the cross-border spread of infectious diseases. Conclusion: China's dengue control and prevention programs provide a compelling case study for the effective application of the One Health approach. By systematically analyzing the integration of multidisciplinary strategies, this review reveals valuable lessons on optimizing public health responses to vector-borne diseases. The alignment of these strategies with One Health principles not only enhances the effectiveness of dengue control efforts in China but also offers a framework that can be adapted by other regions facing similar challenges. Ultimately, the insights gained from this analysis contribute to the global fight against dengue, emphasizing the need for collaborative and holistic approaches in public health initiatives.